Supervised Places to Play: Social reform, citizenship, and femininity at municipal playgrounds in London, Ontario, 1900-1942 - Adams, Carly (Ontario History)

(untitled) (The Ontario Historical Society, 2011)
In early 20th century Canada, middle-class social reformers campaigned for urban parks and supervised playgrounds to provide children with appropriate places for leisure activities. Drawing on adult memories of participating in playgrounds in London, Ontario, this study explores the issues and complexities of establishing the playground program in London and, more specifically, the opportunities provided for girls and young women to learn and play sport. I consider the implications of social and moral reform initiatives on leisure spaces, and the impact of the delivery of social welfare at the municipal level on the lives of female participants.